Relevance of qualifications and work experience in the recruiting of foreign-trained immigrants - comparative insights from the Health and ICT Sectors in Germany and Canada - Annen, Silvia [Verfasser] (My University, 2021)
"Germany and Canada differ significantly regarding their migration policy as well as the structures of the national labour markets and their educational systems. This paper aims to analyse how these differences affect the labour market outcomes of immigrants and the usability of foreign qualifications and work experiences by using the health and ICT sectors as example. The comparison focuses on the question how qualifications and work experience serve as signals and are screened for in the recruiting process of enterprises. The results show clear differences as well as several commonalities between the two compared countries." (author's abstract; BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; P 1.5 Migranten; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; G 1.3.3.1 Qualifikationsverwertung; G 1.2.4.2.8 Gesundheits-, Veterinär- und Sozialwesen; G 1.2.4.2 Dienstleistung; I 2.3.2 Nordamerika; I 2.1 Deutschland; Arbeitsmarkt; Ausländischer Arbeitnehmer; Einwanderer; Auslandsqualifikation; Berufserfahrung; Qualifikationsverwertung; Gesundheitswesen; Informationswirtschaft; Kanada; Bundesrepublik Deutschland